Identification of Breastfeeding Problems using LATCH Score and the Impact of Lactation Counselling: A Quasi-experimental Study - Sandhya Devi Lingala; Nerella Jwala Vasavi; Amara Jyothi Addanki; Lakshmi Prasanna Chintha; Nagireddy Anusha Reddy (Journal of Clinical and Diagnostic Research)
Introduction: Breastfeeding has important positive long-term health consequences for infants and their mothers. Assessing breastfeeding in the early postnatal period, prior to discharge, is crucial for successful breastfeeding. LATCH (Latch, Audible swallowing, Type of nipple, Comfort and Hold) score can be used to categorise mothers with poor breastfeeding scores and counsel them to prevent early breastfeeding cessation. Aim: To identify breastfeeding problems using the LATCH score and to assess the impact of lactation counselling among postnatal mothers. Materials and Methods: This quasi-experimental study was conducted in the Department of Paediatrics, ACSR Government Medical College and Hospital, Nellore, Andhra Pradesh, India, from June 2023 to December 2023. The study included 400 healthy term and singleton babies. LATCH scores were assessed at 6-12 hours after delivery. Mothers with breastfeeding problems were identified, corrected and counselled. The LATCH scores were reassessed again after 24-48 hours. Data were statistically analysed using Chi-square test. The p-value <0.05 was considered to be statistically significant. Results: The average age of the participants was 24.5 years, and most of them were illiterate. Out of 400 mothers, 344 (86%) mother-infant dyads had a LATCH score of <8 at 6-12 hours after delivery; this reduced significantly to 66 (16.5%). at 24-48 hours after breastfeeding support and training (p-value <0.001). Analysis of the association between demographic characteristics and LATCH scores showed that infants of certain subgroups, such as primi, caesarean, young, and less educated mothers, continued to experience lower LATCH scores. Conclusion: The incidence of breastfeeding problems was high during the initial days after childbirth and was particularly prevalent among certain subgroups, such as caesarean mothers, primi-parous mothers, younger mothers and less educated mothers. However, systematic assessment using the LATCH score and timely supportive interventions can significantly improve breastfeeding outcomes.